NGO, Civil Society dan Demokrasi: Kritik atas Pandangan Liberal - - Suharko (Jurnal Ilmu Sosial dan Ilmu Politik, 2003)
By reviewing a variety of studies and research concerning impacts of NGO (Non-Governmental Organizations) activities on civil society empowerment and democracy, the article is a critique of the liberal argument on NGO, civil society and democracy which sees them as having linear and causal relations. On the contrary, it argues that the relationships are much more complex, i.e. involving diverse context and setting. For example, as discussed thoroughly by the author, a number of studies reviewed here confirm that an empowered civil society does not consequentially lead to a consolidated democracy as promoted by the Liberals. Actively operated NGOs –as exemplified by the Philippines case in the article— do not necessarily indicate an active civil society nor an accountable state. In fact, as studies also showed, NGOs would lessen the state capacity in cases where it depends too much to foreign aid.